2006
DOI: 10.4049/jimmunol.177.3.1729
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Residues Are Important in Determining the Binding of Human Monoclonal Antiphospholipid Antibodies to Clinically Relevant Antigens

Abstract: In the antiphospholipid syndrome (APS), antiphospholipid Abs (aPL) bind to anionic phospholipids (PL) and various associated proteins, especially β2-glycoprotein I (β2GPI) and prothrombin. In the present study, we show that altering specific Arg residues in the H chain of a human pathogenic β2GPI-dependent aPL, IS4, has major effects on its ability to bind these clinically important Ags. We expressed whole human IgG in vitro by stable transfection of Chinese hamster ovary cells with expression plasmids contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 61 publications
1
53
0
Order By: Relevance
“…In a previous study (34), we found that alteration of arginines to serines in IS4 V H CDR3 led to an increase in binding to ovalbumin and hypothesized that this might be due to a reversal of serine-to-arginine somatic mutations that took place during affinity maturation. However, we could not be sure of this since the germline sequence corresponding to IS4 V H CDR3 is unknown.…”
Section: Lambrianides Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study (34), we found that alteration of arginines to serines in IS4 V H CDR3 led to an increase in binding to ovalbumin and hypothesized that this might be due to a reversal of serine-to-arginine somatic mutations that took place during affinity maturation. However, we could not be sure of this since the germline sequence corresponding to IS4 V H CDR3 is unknown.…”
Section: Lambrianides Et Almentioning
confidence: 99%
“…Recombinant His 6 -tagged domain I was produced by expression in Escherichia coli, as described elsewhere (33), and direct ELISA for binding to purified recombinant His 6 -tagged domain I was performed as described (33). Monoclonal antibodies were also analyzed by ELISA for binding to ovalbumin, using MaxiSorp microtiter plates (Nunc, Uxbridge, UK), as previously described (34). confers stronger anti-dsDNA and antinucleosome reactivity than the wild-type light chain B3 V L , and we wanted to investigate whether that effect would overcome the negative effect of the R53S change in the heavy chain.…”
Section: Lambrianides Et Almentioning
confidence: 99%
“…Giles and associates (25) from our unit demonstrated that specific R residues located within antigen-binding sites on monoclonal pathogenic aPL are important in determining binding to cardiolipin, whole ␤ 2 GPI, and several other clinically relevant antigens (26). It is possible that these positively charged R residues on aPL may be interacting with anionic residues on domain I of ␤ 2 GPI.…”
mentioning
confidence: 99%
“…Although it is difficult to infer an antibody's specificity based on its amino acid sequence, it has been observed that the CDR‐H3 regions of antibodies in the bone marrow are on average longer, and more hydrophobic than those in the peripheral blood 84,1151,152 , indicating that these CDR‐H3 characteristics are selected against during central tolerance. The charge at the binding site is also critical, the prevalence of positively charged arginines in the CDR3 has been associated with binding to (negatively charged) DNA in some antibodies and in SLE153, 154 and to phospholipid antigens 155. We have shown that the number of arginines, and the other charged amino acids histidine and lysine, can vary significantly between different B cell populations with an overall increase in moving from the naïve to the memory populations,82 perhaps indicating that charged interactions are important for binding to exogenous antigen.…”
Section: Cdr3 Characteristicsmentioning
confidence: 99%